Hubungan Antara Kontrol Diri dengan Perilaku Agresif Pada Remaja di Kelurahan Padang Bulan Kota Medan - Laila Huzna Tarigan; Merri Hafni (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aims to see the negative correlation between self-control and aggressive behavior in adolescents in Padang Bulan Village. The method used in this research is quantitative method. The research subjects used were 100 adolescents aged 12-14 years. The sampling technique used in this research is the purposive sampling technique. The hypothesis proposed in this study is that there is a negative correlation between self-control and adolescent aggressive behavior with the assumption that the higher the self-control, the lower the aggressive behavior. Conversely, the lower the self-control, the higher the aggressive behavior. This study uses a Likert scale to measure the variables of self-control and aggressive behavior. In this study, the data analysis technique used is the Pearson Product Moment Correlation using the SPSS version 25.00 application. Based on the results of the analysis of the data obtained, it shows that there is a negative correlation between self-control and aggressive behavior with a correlation coefficient of -0.672 (rxy = -0.672; P = 0.000). Self-control has an effect of 45.1% on aggressive behavior.